N- and C-terminal Transactivation Domains of GATA1 Protein Coordinate Hematopoietic Program - Kaneko, Hiroshi (American Society for Biochemistry and Molecular Biology, 2012)
Transcription factor GATA1 regulates the expression of a cluster of genes important for hematopoietic cell differentiation toward erythroid and megakaryocytic lineages. Three functional domains have been identified in GATA1, a transactivation domain located in the N terminus (N-TAD) and two zinc finger domains located in the middle of the molecule. Although N-TAD is known as a solitary transactivation domain for GATA1, clinical observations in Down syndrome leukemia suggest that there may be additional transactivation domains. In this study, we found in reporter co-transfection assays that transactivation activity of GATA1 was markedly reduced by deletion of the C-terminal 95 amino acids without significant attenuation of the DNA binding activity or self-association potential. We therefore generated transgenic mouse lines that expressed GATA1 lacking the C-terminal region (GATA1-ΔCT). When we crossed these transgenic mouse lines to the Gata1-deficient mouse, we found that the GATA1-ΔCT transgene rescued Gata1-deficient mice from embryonic lethality. The embryos rescued with an almost similar level of GATA1-ΔCT to endogenous GATA1 developed beyond embryonic 13.5 days, showing severe anemia with accumulation of immature erythroid cells, as was the case for the embryos rescued by endogenous levels of GATA1 lacking N-TAD (GATA1-ΔNT). Distinct sets of target genes were affected in the embryos rescued by GATA1-ΔCT and GATA1-ΔNT. We also found attenuated GATA1 function in cell cycle control of immature megakaryocytes in both lines of rescued embryos. These results thus demonstrate that GATA1 has two independent transactivation domains, N-TAD and C-TAD. Both N-TAD and C-TAD retain redundant as well as specific activities for proper hematopoiesis in vivo.